“Expecting the Unexpected:” Nurses' Response and Preparedness of Terrorism-Related Disaster Events in Quetta City, Pakistan - Khilji, Fazal ur Rehman; Raziq, Abdul; Shoaib, Maryam; Baloch, Nosheen Sikander; Raza, Shanaz; Iqbal, Zaffar; Ishaq, Rabia; Haider, Sajjad; Iqbal, Qaiser; Ahmad, Nafees; Saleem, Fahad (Frontiers in Public Health, 2021)
Background: In addition to the psychiatric and societal misery, terrorism places an exceptional burden while delivering healthcare services. Accordingly, a responsive and well-prepared healthcare system ensures effective management of terrorism-related events. Within this context, with a strong historic grounding in addressing situations of societal crisis nurses are well-placed in contributing to the global arena of humanitarian policy and social research. Therefore, assessing their response and preparedness is vital in effective management of a terrorism-related disaster. For that very reason, we aimed to evaluate nurses' preparedness and response toward terrorism-related disaster events in Quetta city, Pakistan. Methods: A qualitative design was adopted to explore nurses' response and preparedness of terrorism-related disaster events. By using a semi-structured interview guide through the phenomenology-based approach, in-depth, face-to-face interviews were conducted. Nurses practicing at the Trauma Center of Sandeman Provincial Hospital (SPH), Quetta, were approached for the study. All interviews were audio-taped, transcribed verbatim, and were then analyzed for thematic contents by the standard content analysis framework. Results: Fifteen nurses were interviewed and thematic content analysis revealed five themes. All nurses have experienced, responded to, and managed terrorism-related disaster events. They were prepared both professionally and psychologically in dealing with a terrorism-related disaster. Among limitations, space and workforce were highlighted by almost all the respondents. Lack of disaster-related curricula, absence of a protocol, recurrence of the disaster, and hostile behavior of victim's attendants during an emergency were highlighted as a key barrier toward terrorism-related disaster management. Conclusion: The skills and expertise needed to address a terrorism-related disaster are well-understood by the nurses but are lacking for various reasons. In addition to the review and adaption of the nursing curriculum specifically for terrorism-related disaster management, collaboration and dialogue between various stakeholders is required to efficiently manage terrorism-related disaster events.